Perancangan Aplikasi Absensi Pegawai di Hotel OYO 387 Alfa Guest House Berbasis Web - Adi Febriasnyah; Aziz Firmansyah; M. Fathin Fadhil; Dani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Absence in general is the recording of employee attendance and is one aspect of an assessment in a company. OYO Rooms or called OYO 387 Alfa Guest House is a company engaged in the field of lodging services. The system used in the employee attendance process at OYO 387 Alfa Guest House is still manual, namely by recording an attendance book. This of course has an impact on the effectiveness and efficiency of data collection, data search, and calculating attendance recap which takes time, so that the risk of errors will increase the loss of attendance data. For this reason, an application is needed that is used for attendance and at the same time reports related to employee attendance data. Data collection methods used in this study include observation, interviews and literature study. The development method used is the waterfall method which includes: analysis, design, coding, testing. By producing a web-based employee attendance application, it can provide convenience in the attendance process, data search and minimize loss and errors in recording attendance data at Hotel OYO 387 Alfa Guest House.